1992
DOI: 10.1111/j.1476-5381.1992.tb14501.x
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of the ischaemic myocardium; involvement of the l‐arginine nitric oxide pathway

Abstract: 1 Short periods of coronary artery occlusion protect the heart against the effects of a subsequent prolonged period of ischaemia. This phenomenon is known as preconditioning of the ischaemic myocardium. 2 In mongrel, chloralose-urethane anaesthetized open-chest dogs, within a restricted body weight range, two 5 min periods of occlusion of the anterior descending branch of the left coronary artery markedly reduced the severity of the early ischaemic arrhythmias resulting from a prolonged (25 min) occlusion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
1
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(166 citation statements)
references
References 19 publications
12
150
1
3
Order By: Relevance
“…Among these substances, NO has been recognised as having pronounced beneficial effects, owing to its powerful vasodilator action (Rubanyi et al, 1991;Vegh et al, 1992). The newly recognised property of RLX to stimulate NO production in perfused hearts suggests that this hormone may play an important role in the regulation of myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Among these substances, NO has been recognised as having pronounced beneficial effects, owing to its powerful vasodilator action (Rubanyi et al, 1991;Vegh et al, 1992). The newly recognised property of RLX to stimulate NO production in perfused hearts suggests that this hormone may play an important role in the regulation of myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, potential mediators include nitric oxide (NO) 2,4 and adenosine. 5 Vegh et al 6 reported that the protection conferred by preconditioning in dog heart in vivo disappeared after NO inhibition. Nevertheless, other authors 7 found that endogenous NO is not a mediator in the ischemic preconditioning in the isolated rat heart.…”
mentioning
confidence: 99%
“…Furthermore, since many of the beneficial effects of statins are thought to be mediated via the synthesis of nitric oxide (Laufs et al, 1997;Laufs and Liao, 1998), and since we have a number of previous evidence that NO plays an essential role in the protection against the ischaemia-induced early arrhythmias (e.g. Végh et al, 1992b;Kis et al, 1999), we have now also examined whether the effect of simvastatin on arrhythmias involves the activation of eNOS and the subsequent increase in NO formation.…”
Section: Discussionmentioning
confidence: 99%
“…We have substantial previous evidence that NO plays an essential role in both the early and delayed anti-arrhythmic effects of preconditioning, induced either by brief periods of coronary artery occlusion (Végh et al, 1992b), cardiac pacing (Kis et al, 1999) or heavy physical exercise (Babai et al, 2002). We hypothesized that these preconditioning stimuli, via the activation of eNOS, enhance NO production and modify myocardial function during ischaemia and reperfusion (Parratt and Végh, 1996).…”
Section: Introductionmentioning
confidence: 99%